2013
DOI: 10.1371/journal.pone.0078043
|View full text |Cite|
|
Sign up to set email alerts
|

Doxorubicin-Mediated Bone Loss in Breast Cancer Bone Metastases Is Driven by an Interplay between Oxidative Stress and Induction of TGFβ

Abstract: Breast cancer patients, who are already at increased risk of developing bone metastases and osteolytic bone damage, are often treated with doxorubicin. Unfortunately, doxorubicin has been reported to induce damage to bone. Moreover, we have previously reported that doxorubicin treatment increases circulating levels of TGFβ in murine pre-clinical models. TGFβ has been implicated in promoting osteolytic bone damage, a consequence of increased osteoclast-mediated resorption and suppression of osteoblast different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…Moreover, in a preclinical murine model of breast cancer, doxorubicin induced a significant decrease in TBV and increased serum markers of bone resorption. These phenomena were also observed in non-tumor bearing mice, suggesting that the bone health impairment was tumor independent [45].…”
Section: Doxorubicinmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, in a preclinical murine model of breast cancer, doxorubicin induced a significant decrease in TBV and increased serum markers of bone resorption. These phenomena were also observed in non-tumor bearing mice, suggesting that the bone health impairment was tumor independent [45].…”
Section: Doxorubicinmentioning
confidence: 66%
“…Besides its cardiotoxic and myelosuppressive effects, doxorubicin may compromise the bone health by increasing OC differentiation and reducing fibroblast and OB forming units that derive from BMSCs, as described in vitro by Rana et al [45]. These effects are mediated by oxidative stress, confirmed by superoxide dismutase downregulation, and partially abrogated by an anti-TGFb antibody, suggesting that there is also a hyperactivation of the TGFb pathway in doxorubicin-treated cells.…”
Section: Doxorubicinmentioning
confidence: 92%
“…In particular, preclinical studies of breast cancer bone metastases have shed much light on this topic. Doxorubicin and carboplatin chemotherapies have been used to study musculoskeletal changes and have revealed that these agents alone cause significant reduction in bone volume . The combination therapy Folfiri (5‐fluorouracil, leucovorin, and irinotecan) also causes reduced bone volume …”
Section: Bone Loss In Cancer Patientsmentioning
confidence: 99%
“…Although there are many therapeutic strategies, more than one million new cases of breast cancer are diagnosed every year [3]. Some of the main problems in the treatment of cancer are high cytotoxicity and drug resistance, and no clinically active substances are known to act selectively on tumor cells.…”
Section: Introductionmentioning
confidence: 99%